Visual interpretation, not SUV ratios, is the ideal method to interpret 18F-DOPA PET scans to aid in the cure of patients with focal congenital hyperinsulinism - Garg, Pradeep K. (PLoS One, 2020)
INTRODUCTION: Congenital hyperinsulinism is characterized by abnormal regulation of insulin secretion from the pancreas causing profound hypoketotic hypoglycemia and is the leading cause of persistent hypoglycemia in infants and children. The main objective of this study is to highlight the different mechanisms to interpret the (18)F-DOPA PET scans and how this can influence outcomes. MATERIALS AND METHODS: After (18)F-Fluoro-L-DOPA was injected intravenously into 50 subjects’ arm at a dose of 2.96–5.92 MBq/kg, three to four single-bed position PET scans were acquired at 20, 30, 40 and 50-minute post injection. The radiologist interpreted the scans for focal and diffuse hyperinsulinism using a visual interpretation method, as well as determining the Standard Uptake Value ratios with varying cut-offs. RESULTS: Visual interpretation had the combination of the best sensitivity and positive prediction values. CONCLUSIONS: In patients with focal disease, SUV ratios are not as accurate in identifying the focal lesion as visual inspection, and cases of focal disease may be missed by those relying on SUV ratios, thereby denying the patients a chance of cure. We recommend treating patients with diazoxide-resistant hyperinsulinism in centers with dedicated multidisciplinary team comprising of at least a pediatric endocrinologist with a special interest in hyperinsulinism, a radiologist experienced in interpretation of (18)F-Fluoro-L-DOPA PET/CT scans, a histopathologist with experience in frozen section analysis of the pancreas and a pancreatic surgeon experienced in partial pancreatectomies in patients with hyperinsulinism.